Investigation of the Rearrangement of Reactive–Inert Particulate Structures in a Single Channel of a Wall-Flow Filter - Julia R. D. Thieringer; Nicolas Hafen; Jörg Meyer; Mathias J. Krause; Achim Dittler (Separations, 2022)
Wall-flow filters are a standard component in exhaust gas aftertreatment and have become indispensable in vehicles. Ash and soot particles generated during engine combustion are deposited in diesel or gasoline particulate filters. During regeneration, the soot particles are oxidized. The remaining ash particles can form different deposition patterns: a homogenous layer or plug-end filling. It has not yet been clarified whether the plug-end filling is first formed by rearrangements of agglomerates before and during the regeneration of the reactive particles. In this study, experiments are carried out with a single channel of a wall-flow filter. For the investigations, a layer of inert and reactive particles is formed. The rearrangement of agglomerates is achieved by flowing through the model filter channel and observed with a high-speed camera. The particulate structures detach at the channel inlet, are transported along the channel and deposited at the plug. The velocity of the detached agglomerates depends on their size, shape, track and the gas velocity in the channel. If the agglomerate is near the walls of the model filter channel, the gas velocity deviates from the gas velocity in the core flow. The higher the gas velocity, the higher the agglomerate velocity achieved and the larger the detached agglomerates.